Recent root canal irrigation protocol followed by endodontists and postgraduate students of endodontics for root canal therapy in Central India: A survey - Rajeshwar Singh; Mona Agrawal; Sachin Thakur; Trapti Sharma; Abhishek Sinha; Rahul A Razdan (Wolters Kluwer Medknow Publications, 2022)
Background: One of the main purposes of root canal treatment is the complete debridement of root canals. Regardless of the instrumentation technique used 35% or more of the root canal surfaces have been observed to remain uninstrumented. To remove debris and address these uninstrumented surfaces, it is necessary to copiously irrigate the root canal. Many adjuncts have also been developed and being used in an effort to improve the delivery and effectiveness of these irrigants. Although much research have been conducted on different root canal treatment regime and irrigants used in dentistry, only a little data can be found on the widespread practice or acceptance of such methods. Aims and Objectives: The purpose of this survey was therefore to ascertain the current trends in the use of root canal irrigants and irrigation protocol followed by Endodontists and Postgraduate students across Central India (Madhya Pradesh). Material and Methods: A questionnaire-based survey was conducted and participants were asked to fill in responses to some questions regarding their preferences for root canal irrigation like irrigant selection, irrigant concentration, technique used for delivery and activation of irrigants, etc. Results: The majority of the respondents considered both irrigations as well as instrumentation to be of equal importance. Also, the majority of respondents prefer full-strength sodium hypochlorite (5.25%) while only a few have been found to use its lower concentration (3%). Conclusion: It is essential for future prospects to get an awareness of the properties and actions of irrigants and incorporate them into practice for executing a successful endodontic treatment.